The relationship between nutritional status and the incidence of hypertension at primary health care facilities in the working area of bojongsoang community health center, bandung regency, 2025 - Muhamad Rosyid Kusdiawan; Mia Miranda Sitti; Helmi Rosa Gunadi (Science Midwifery, 2026)
Background: Hypertension is a major public health problem that increases the risk of cardiovascular disease, stroke, and renal failure. Nutritional status, particularly overweight and obesity, is one of the contributing factors to hypertension. The prevalence of hypertension and overnutrition in the working area of Bojongsoang Primary Health Care remains high, making it necessary to assess their relationship. Methods: This study used a cross-sectional design with secondary data obtained from a previous study. A total of 135 respondents who met the inclusion and exclusion criteria at primary health care facilities in the working area of Bojongsoang Health Center, Bandung Regency, in 2025 were included. Nutritional status was determined using Body Mass Index (BMI), and hypertension status was classified as controlled and uncontrolled. Data were analyzed using univariate analysis and bivariate analysis with the Chi-Square test. Results: Most respondents were classified as obese (42.2%) and overweight (17.8%). The majority of respondents had uncontrolled hypertension (65.9%). Bivariate analysis showed a significant association between nutritional status and the incidence of hypertension (p < 0.05), with overweight and obese respondents having a higher proportion of uncontrolled hypertension compared to those with normal or underweight nutritional status. Conclusion: There is a significant relationship between nutritional status and the incidence of hypertension in primary health care facilities in the working area of Bojongsoang Health Center, Bandung Regency, in 2025. Nutritional status control, particularly the prevention of overweight and obesity, should be an essential component of hypertension management and prevention strategies.